THE EFFECT OF AUDITEE CHARACTERISTICS AND AUDIT TENURE ON AUDIT OPINION IN BANKING COMPANIES LISTED ON THE INDONESIAN STOCK EXCHANGE - Dewi, Azzahra Aulia; Nugroho, Dwiyanjana Santyo (CV. Fahr Publishing, 2023)
Increased investment activity makes the use of financial statements and audit opinions on financial statements also increase. This is because investors will pay attention to the opinion before investing in order to get confidence and know the reliability of information in the financial statements. This study aims to determine empirically the effect of institutional ownership, current ratio, operating margin to total asset ratio, and audit tenure on audit opinion in banking companies listed on the Indonesia Stock Exchange in 2020 - 2022. This study uses quantitative methods, researchers tested and analyzed 102 samples consisting of 34 banking companies selected by purposive sampling method and analyzed using logistic regression. The results of this study indicate that institutional ownership and current ratio have an effect on audit opinion, while operating margin to total asset ratio and audit tenure have no effect on audit opinion. This study only examines banking companies and only uses financial statements for 2020-2022 to see changes in conditions during the covid-19 pandemic to the recovery period from the covid-19 pandemic. Researchers hope that this research can be a source of reading and become a reference material for investors who want to invest in banking companies.